The Exploratory Impact of Technology, Organizational Concepts, and Employee Training on Business Performance - Heilala, Janne; Salminen, Antti; Bessa, Wallace Moreira; Kantola, Jussi (EJournal Publishing, 2025)
This paper analyzes exploratory, the findings from Finland's 2022 European Manufacturing Survey (EMS22). The primary focus is on the narrowed Development of Competitiveness and Employment Situations (DCES) measures, measured by parameters such as Annual Turnover (AT), Number of Employees (NE), Manufacturing Capacity Utilization (MCU), and Return on Sales (ROS). The interaction between Organizational Concepts (OCs) and Key Enabling Technologies (KETs) is explored in the context of manufacturing, with attention to Organizing Production (OP), Production Management and Control (PMC), Training and Competency Development (TCD), Production Control (PC), Automation and Robotics (AR), Efficiency Technologies (ET), and Simulation Data Analysis and Additive Manufacturing (SDA). The investigation seeks to understand how OCs and KETs interplay with the key components of DCES in the EMS22 environment. Results illustrate the influence of these aspects on AT and NE, with significant implications for MCU and ROS. Interestingly, the impact of PMC on ROS was marginal, suggesting a contentious relationship. TCD appears to play a supporting role in this context.